THE IMPLICATIONS OF TERRORIST ATTACKS OVER TOURISM IN ROMANIA AND THE EUROPEAN UNION - Liviu MĂRCUȚĂ; Maria STOIAN; Cristina TINDECHE; Alina MĂRCUȚĂ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
We live in a world where globalization is increasingly spoken about and its role in the development of humanity, where local economies and social groups have become the exponents of a dynamic system, being interconnected through communications, transport and commerce. All these elements have made humanity a very complex system, but vulnerable due to the economic, technological, socio-cultural, political and biological factors that contributed to the emergence of asymmetric threats to global security. One of these threats is terrorism. This paper proposes an analysis of the effects that terrorist attacks have had on the European Union tourism, given the large and increasing number of these attacks. Tourism offers the opportunity to visit, discover, know, observe how other civilizations live, is an important engine of the economy, but at the same time it is very sensitive to events that can affect personal safety. Thus, after taking over the statistical data on tourist traffic, data provided by Eurostat and the National Institute of Statistics in Bucharest, we analyzed and interpreted this information, which gave us some conclusions regarding the way in which the terrorist attacks affected the personal safety of tourists and how they influenced their choices.